أسباب التكييف الخاطئ في الدعوى المدنية: دراسة مقارنة - جادر، غنى ريسان; كاطع، زمن فوزي (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2018)
تبدأ الدعوى المدنية بطلب يقدمه المدعي الى القاضي وتنتهي بصدور الحكم فيها والحكم العادل هو الغاية التي ينشدها المدعي من رفع دعواه لكن الوصول الى هذا الحكم ليس بالأمر السهل لان الن ا زع المرفوع أمام القاضي يتكون من مجموعة من العناصر والوقائع المنتجة والغير منتجة ووسائل الدفاع والهجوم بالإضافة الى ما تتميز به القواعد القانونية من العمومية والتجريد والتي تتناول أعداد من الحوادث لا حصر لها ولما كانت هذه الحوادث لا تقوم الا معينة ولكل منها خصوصية لا توجد في غيره ومن ثم يجب على القاضي أن يدخل هذه الحوادث تحت طائلة أحدى هذه النصوص، والموضوع قد يكون سهلاً او صعباً وهو كله اجتهاد ونظر وهو ما أطلق عليه بالتكييف ومن ثم فأن الوصول للحكم العادل ليس ميسوراً على القاضي لذلك أوجد النظام القانوني ما يسمى بتكييف الدعوى وهو يعتبر وسيلة القاضي للوصول الى الحكم في الدعوى فالتكييف هو انزال حكم القانون على الوقائع. والدعوى المدنية تتكون من عنصرين هما الواقع والقانون حيث يعتبران جناحي الدعوى المدنية ومن واجب الخصوم تقديم الوقائع للمحكمة واثباتها ومهمة القاضي هو إعطاء هذه الوقائع اسماً قانونياً ينطبق عليها اي بمعنى آخر ردها الى القاعدة القانونية الواجبة التطبيق عليها وهو ما يعرف بالتكييف ومن ثم فأن التكييف الخاطئ يحدث أما بسبب الخصوم نتيجة عدم الدقة في تعيين وقائع الدعوى أو بسبب عدم إتباع إجراءات الاثبات المنصوص عليها في القانون. والتكييف القانوني كقاعدة عامة هو من واجب المحكمة حيث يجب على القاضي أن يكيف الدعوى التكييف الصحيح تاركاً تكييف الخصوم جانباً لذلك يقع التكييف الخاطئ بسبب المحكمة اما بسبب عدم الدقة في تقدير وقائع الدعوى او بسبب الخطأ في تطبيق نصوص القانون وقواعد القانون الاخرى.
The civil procedure begins when the plaintiff presents a lawsuit to the judge it is ended by issuing the adjudication. The fair adjudication is the purpose of the plaintiff from his lawsuit, but to reach this adjudication is not easy because the dispute which is submitted to the judge including a group of elements, the productive and nonproductive events, defense and attack means. In addition, it includes legal rules of generalization and divestiture which tackle with number of unlimited events since these events are specific and they have their own uniqueness so the judge should put these events within the rule of these text, the subject may be easy or difficult and it is all based on diligent and opinion which is called adaptation, then reaching the fair adjudication is not easy for the judge so he finds what is called litigation characterization which is considered as the judge means to apply the law provision on events. Civil procedure consists of two elements which are the reality and law which consider as the wings of civil procedure. The litigants shall present the facts to the court and prove them and the judge's task is to give those facts a legal name: in other words, it means to take them back to lawful rule that is necessary to be applied, which is known by characterization and then the false characterization happens either the litigants as a result to the lack in identifying the facts or un following the proof procedures of the law. Lawful characterization as a general rule is the court duty which means the judge shall characterize the lawsuit correctly leaving the litigant characterization aside so that the false characterization happens because of the court, because the lack of precision of litigation appointing or the fault in applying the law provisions and other law rules
Keywords: القوانين والتشريعات -- الدعوى المدنية -- التكييف القانونى -- التشريعات الاجرائية